In This Issue - Michael Scriven (The Evaluation Center at Western Michigan University, 2006)
In this issue, we have some methodological reflections from another valorous (female) evaluator working successfully on the HIV/AIDS front in the darkest reaches of the Amazon jungle, with a largely law-breaking clientele whose general attitude about any breach of confidentiality seems to have been that it would probably cause their death, so why not yours as well. The article is a kind of handbook of hazards for evaluators working 'in harm's way' and hence a good guide to planning for others. Interestingly, it may provide the strongest argument for empowerment evaluation: do it when it's the only possibility.